"Laboratory Evaluation of Urine Culture and Drug Resistance in Childern Clinically Suspected of Urinary Tract Infection (UTI)" - F Vaezzadeh; MK Sharifi-Yazdi (Tehran University of Medical Sciences, 2001)
Urine specimens from 6656 children clinically suspected of urinary tract infection were evaluated bacteriologically. Bacterial colony count of over (103) colony forning units CFU/ ml were found in 480 (7.2%) of total cases, with 342 (71.25%) girls and 138 (28.75%) boys. Bacterial etiology of positive culture were determind. Escherichia coli was the most frequent etiologic agent (75.62%) followed by klebsiella species (7.32%). The antimicrobial resistance behaviour of Escherichia coli to routinely used antibiotics were tested. Most strains of Escherichia coli were resistant to cotrimoxazole (82%) and ampicillin (82%), but none of them were resistant to ceftizoxime. Correlation between positive urine culture and pyuria for the diagnosis of UTI was compared. It was noted that approximately 38% of paitents with positive urine culture did not have pyuria.